2018
DOI: 10.1617/s11527-018-1148-5
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of cement pastes into sand packings during 3D printing: analytical and experimental study

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 23 publications
2
60
0
4
Order By: Relevance
“…Abhängig von den für den Druckprozess verwendeten Materialien können zwei selektiv bindende Partikelbett‐3‐D‐Druckverfahren unterschieden werden: (1) die selektive Leimintrusion, bei der das Partikelbett aus Gesteinskörnung (≤ 5 mm) ohne Bindemittel besteht und Bindemittelleim selektiv auf das Partikelbett aufgetragen wird (Bild b) und (2) die selektive Zementaktivierung, bei der das Partikelbett aus sehr feiner Gesteinskörnung (Sand < 1 mm) und Zement besteht und der Zement lokal durch Wasser aktiviert wird (Bild c). Die selektiv bindenden Partikelbett‐3‐D‐Druckverfahren werden derzeit u. a. an der TU München und der TU Braunschweig grundlegend erforscht und von D‐Shape kommerziell eingesetzt.…”
Section: Grundlegende Prinzipien Der Additiven Fertigungunclassified
“…Abhängig von den für den Druckprozess verwendeten Materialien können zwei selektiv bindende Partikelbett‐3‐D‐Druckverfahren unterschieden werden: (1) die selektive Leimintrusion, bei der das Partikelbett aus Gesteinskörnung (≤ 5 mm) ohne Bindemittel besteht und Bindemittelleim selektiv auf das Partikelbett aufgetragen wird (Bild b) und (2) die selektive Zementaktivierung, bei der das Partikelbett aus sehr feiner Gesteinskörnung (Sand < 1 mm) und Zement besteht und der Zement lokal durch Wasser aktiviert wird (Bild c). Die selektiv bindenden Partikelbett‐3‐D‐Druckverfahren werden derzeit u. a. an der TU München und der TU Braunschweig grundlegend erforscht und von D‐Shape kommerziell eingesetzt.…”
Section: Grundlegende Prinzipien Der Additiven Fertigungunclassified
“…In order to avoid this procedure in future, prediction of the penetration depth of the cement paste by means of simple material tests and analytical models is required. A first approach of an analytical model to calculate the penetration of cement pastes into particle-beds by Pierre et al [ 44 ] showed good results to predict a penetration of the cement paste into the particle-bed under the assumption that the penetration ends at the border to the next layer of the particle-bed. Moreover, numerical simulation appears to be an alternative for the prediction of the penetration depth [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents analytical models which are able to calculate penetration depths which are even deeper than a particle-bed layer. Furthermore, the models in this paper try to take the flow behavior during the application of the cement paste on the particle-bed into account, before the penetration starts, which enables a slight modification of a model already existing by Pierre et al [ 44 ] (model A) to be used for penetration depths greater than the layer height (model A+). Additionally, a new approach for an analytical implementation of the pore structure of the particle-bed and of the process-parameters of the printer (applied volume as well as nozzle diameter) are considered.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cement grouts have also been used for 3D printing operations by selective paste intrusion [15,16]. During the injections, the cement grout must be fluid enough to fill a cavity or to penetrate into a porous network.…”
Section: Introductionmentioning
confidence: 99%